Krótki komentarz do kilku terminów urobionych od rzeczownika „karyke” (ĸαρύκη) - Kokoszko, Maciej (Przegląd Nauk Historycznych, 2008)
The present article discusses meanings of a number of terms which were coined in antiquity and still used in Byzantium, and which originated with the name of a famous delicacy called karyke. The author comes to the conclusion that the terms were only loosely connected with the delicacy itself and were used to denote the general activity of preparing foods, and especially to the process of spicing. The majority of usages of the analyzed verbs suggest that there was a prevalent tendency to use the terms figuratively, and thereby the verbs lost their direct connection with the mere subject of Greek cuisine.